December dog - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2014)
After finding an unusual present--a lost puppy--on Christmas Eve, best friends Bradley, Brian, Nate, and Lucy scramble to find its owner before morning
"A Stepping Stone book."
Ages 6-9
Accelerated Reader AR
Reading Counts RC
Keywords: Puppies -- Juvenile fiction; Dogs -- Juvenile fiction; Animals -- Infancy -- Juvenile fiction; Gifts -- Juvenile fiction; Mystery and detective stories; Dogs -- Fiction; Animals -- Infancy -- Fiction; Christmas -- Fiction; Gifts -- Fiction; Christmas stories; Mystery and detective stories; Detective and mystery fiction